(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper provides a synthesis of research on magnetic springs with variable stiffness that can be the basis for obtaining configurations of electromechanical systems whose operation requires fixed or real-time adjustable pre-established elastic forces, such as vibration damping or humanoid and medical recovery robots. The study and systematization of the research known up to this point highlights the basic concepts and specific characteristics for the two main categories of magnetic springs with variable stiffness, namely, passive magnetic springs with a predetermined stiffness at a desired value (ASMSs) and active magnetic springs with real-time adjustable stiffness (CSEMSs). The study highlights that CSEMSs that generate variable stiffness in a very wide range, from ˗˗9800 N/m to +9800 N/m, can be obtained, which makes them very useful in the design and construction of systems for controlling fast processes, such as vibration isolation systems with quasi-zero-stiffness (QZS).